Cardiovascular disease prevention in rural Nigeria in the context of a community based health insurance scheme: QUality Improvement Cardiovascular care Kwara-I (QUICK-I) - Alli Shade; Vollaard Albert; Bindraban Navin; Redekop William; Odusola Aina; Bolarinwa Oladimeji; Wit Ferdinand; Brewster Lizzy; Hendriks Marleen; Adenusi Peju; Agbede Kayode; Akande Tanimola; et al. (BMC, 2011)
Abstract Background Cardiovascular diseases (CVD) are a leading contributor to the burden of disease in low- and middle-income countries. Guidelines for CVD prevention care in low resource settings have been developed but little information is available on strategies to implement this care. A community health insurance program might be used to improve patients' access to care. The operational research project "QUality Improvement Cardiovascular care Kwara - I (QUICK-I)" aims to assess the feasibility of CVD prevention care in rural Nigeria, according to international guidelines, in the context of a community based health insurance scheme. Methods/Design Design: prospective observational hospital based cohort study. Setting: a primary health care centre in rural Nigeria. Study population: 300 patients at risk for development of CVD (patients with hypertension, diabetes, renal disease or established CVD) who are enrolled in the Hygeia Community Health Plan. Measurements: demographic and socio- economic data, physical and laboratory examination, CVD risk profile including screening for target organ damage. Measurements will be done at 3 month intervals during 1 year. Direct and indirect costs of CVD prevention care will be estimated. Outcomes: 1) The adjusted cardiovascular quality of care indicator scores based on the "United Kingdom National Health Services Quality and Outcome Framework". 2) The average costs of CVD prevention and treatment per patient per year for patients, the clinic and the insurance company. 3) The estimated net health care costs of standard CVD prevention care per quality-adjusted life year gained. Analysis: The primary outcomes, the score on CVD quality indicators and cost data will be descriptive. The quality scores and cost data will be used to describe the feasibility of CVD prevention care according to international guidelines. A cost-effectiveness analysis will be done using a Markov model. Discussion Results of QUICK-I can be used by policy makers and professionals who aim to implement CVD prevention programs in settings with limited resources. The context of the insurance program will provide insight in the opportunities community health insurance may offer to attain sustainable chronic disease management programs in low resource settings. Trial registration This protocol has been registered at ISRCTN, ID number: ISRCTN47894401.